The Bacterial Extracellular Matrix Protein TapA Is a Two‐Domain Partially Disordered Protein. (13th December 2018) - Abbasi, Razan; Mousa, Reem; Dekel, Noa; Amartely, Hadar; Danieli, Tsafi; Lebendiker, Mario; Levi‐Kalisman, Yael; Shalev, Deborah E.; Metanis, Norman; Chai, Liraz
Abstract: Biofilms are aggregates of microbial cells that form on surfaces and at interfaces, and are encased in an extracellular matrix. In biofilms made by the soil bacterium Bacillus subtilis, the protein TapA mediates the assembly of the functional amyloid protein TasA into extracellular fibers, and it anchors these fibers to the cell surface. We used circular dichroism and NMR spectroscopy to show that, unlike the structured TasA, TapA is disordered. In addition, TapA is composed of two weakly interacting domains: a disordered C‐terminal domain and a more structured N‐terminal domain. These two domains also exhibited different structural changes in response to changes in external conditions, such as increased temperatures and the presence of lipid vesicles. Although the two TapA domains weakly interacted in solution, their cooperative interaction with lipid vesicles prevented disruption of the vesicles. These findings therefore suggest that the two‐domain composition of TapA is important in its interaction with single or multiple partners in the extracellular matrix in biofilms. Abstract : Falling in line : The extracellular matrix protein TapA is a partially disordered protein composed of two weakly interacting domains: N‐terminal domain (NTD; purple) and C‐terminal domain (CTD; green). These fragments gain structure with increasing temperature and in the presence of lipid vesicles.